Pure word deafness due to bilateral temporal lobe ischemic stroke occurring at different time points over the years: a case report on the insight of brain language network reorganization. Issue 1 (2nd January 2021) - Virvidaki, Ioanna‐Eleni; Messinis, Lambros; Nasios, Grigorios
ABSTRACT: Here we present a case of a native Greek male patient who presented clinically with sudden onset pure word deafness after an ischemic stroke in the temporoparietal region of the right hemisphere, but who had suffered an ischemic stroke 9 years previously in an adjacent area of the left hemisphere, causing aphasic symptoms which resolved quickly and almost completely. What makes this case interesting and novel is that it is the first case describing a patient whose ventral language comprehension circuit did not reorganize successfully due to damage of the adjacent right hemisphere language areas at a subsequent time.